Simultaneous assessment of serum levels and pharmacologic effects of cannabinoids on endocannabinoids and N-acylethanolamines by liquid chromatography-tandem mass spectrometry - Couttas, Timothy; Boost, Carola; Pahlisch, Franziska; Sykorova, Eliska; Leweke, Judith E.; Köthe, Dagmar; Endepols, Heike; Rohleder, Cathrin; Leweke, F. Markus (Cannabis and cannabinoid research, 2023)
Introduction: The primary compounds of Cannabis sativa, delta-9-tetrahydrocannabinol (Δ9-THC) and cannabidiol (CBD), inflict a direct influence on the endocannabinoid system-a complex lipid signaling network with a central role in neurotransmission and control of inhibitory and excitatory synapses. These phytocannabinoids often interact with endogenously produced endocannabinoids (eCBs), as well as their structurally related N-acylethanolamines (NAEs), to drive neurobiological, nociceptive, and inflammatory responses. Identifying and quantifying changes in these lipid neuromodulators can be challenging owing to their low abundance in complex matrices. - Materials and Methods: This article describes a robust liquid chromatography-tandem mass spectrometry (LC-MS/MS) method for the extraction and quantification of the eCBs anandamide and 2-arachidonoylglycerol, along with their congener NAEs oleoylethanolamine and palmitoylethanolamine, and phytocannabinoids CBD, Δ9-THC, and 11-Nor-9-carboxy-Δ9-tetrahydrocannabinol, a major metabolite of Δ9-THC. Our method was applied to explore pharmacokinetic and pharmacodynamic effects from intraperitoneal injections of Δ9-THC and CBD on circulating levels of eCBs and NAEs in rodent serum. - Results: Detection limits ranged from low nanomolar to picomolar in concentration for eCBs (0.012-0.24 pmol/mL), NAEs (0.059 pmol/mL), and phytocannabinoids (0.24-0.73 pmol/mL). Our method displayed good linearity for calibration curves of all analytes (R2>0.99) as well as acceptable accuracy and precision, with quality controls not deviating >15% from their nominal value. Our LC-MS/MS method reliably identified changes to these endogenous lipid mediators that followed a causal relationship, which was dependent on both the type of phytocannabinoid administered and its pharmaceutical preparation. - Conclusion: We present a rapid and reliable method for the simultaneous quantification of phytocannabinoids, eCBs, and NAEs in serum using LC-MS/MS. The accuracy and sensitivity of our assay infer it can routinely monitor endogenous levels of these lipid neuromodulators in serum and their response to external stimuli, including cannabimimetic agents.
Im Titel ist der Buchstabe "N" bei "N-acylethanolamines" in kursiver Schrift geschrieben
Gesehen am 18.06.2024